The Qur’an as a Living Text: Reception Hermeneutics across Muslim Traditions and Digital Spaces - Isnaeni, Ahmad; Yanti, Asri; Indah, Ayu; Kurniasih, Dini; Hany, Wafiq; Urbaningrum A, Anastasya (Jurnal Pemikiran Islam, 2026)
This article examines the Qur’an as a living text through reception hermeneutics, with attention to transformations in Qur’anic reception from Muslim traditions to digital environments. It treats the Qur’an as a source of meaning enacted through readers’ engagements, ritual practices, cultural expressions, social ethics, and intellectual production. The article employs qualitative library research, drawing on scholarship on living Qur’an, reception theory, Qur’anic hermeneutics, and digital religion. The analysis identifies five interconnected forms of Qur’anic reception in Muslim traditions: textual, ritual, cultural-aesthetic, social, and intellectual. Digital media extend these forms through Qur’an applications, social media, online learning, visual content, and interactive platforms. This shift reshapes relations among text, readers, media, and religious authority by expanding access and participation while exposing Qur’anic messages to decontextualization, fragmented authority, and visibility-driven circulation. Reception hermeneutics provides a conceptual framework for examining how Qur’anic meaning is received, enacted, circulated, and negotiated in contemporary Muslim societies. The analysis also indicates the need for attention to source integrity, interpretive validity, and digital religious literacy in contemporary Qur’anic studies.